2012
DOI: 10.3389/fpls.2012.00080
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis CstF64-Like RSR1/ESP1 Protein Participates in Glucose Signaling and Flowering Time Control

Abstract: Mechanisms for sensing and regulating metabolic processes at the cellular level are critical for the general physiology and development of living organisms. In higher plants, sugar signaling is crucial for adequate regulation of carbon and energy metabolism and affects virtually every aspect of development. Although many genes are regulated by sugar levels, little is known on how sugar levels are measured by plants. Several components of the sugar signaling network have been unraveled and demonstrated to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Thus far, several components have been proposed to be involved in various Suc signaling processes. For instance, the protein kinase Suc nonfermenting related kinase-1 (SnRK1) is required for Suc signal transduction, leading to starch synthesis and Suc synthase induction in potato (Tiessen et al, 2003); the REDUCED SUC RESPONSE 1 (RSR1) was identified as a critical factor for Suc signaling during seed germination and early seedling development (Funck et al, 2012); the SUC UNCOUPLED 6 (SUN6) is involved in the Suc-mediated down-regulation of photosynthesis genes (Dijkwel et al, 1997); and the IMPAIRED SUC INDUCTION 4 (ISI4) is required for Suc-mediated growth inhibition (Laby et al, 2000). Here, we investigated whether the regulation of Fe deficiency responses by Suc was associated with the aforementioned Suc signaling components by using snrk1.1, snrk1.2, rsr1, sun6, and isi4 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, several components have been proposed to be involved in various Suc signaling processes. For instance, the protein kinase Suc nonfermenting related kinase-1 (SnRK1) is required for Suc signal transduction, leading to starch synthesis and Suc synthase induction in potato (Tiessen et al, 2003); the REDUCED SUC RESPONSE 1 (RSR1) was identified as a critical factor for Suc signaling during seed germination and early seedling development (Funck et al, 2012); the SUC UNCOUPLED 6 (SUN6) is involved in the Suc-mediated down-regulation of photosynthesis genes (Dijkwel et al, 1997); and the IMPAIRED SUC INDUCTION 4 (ISI4) is required for Suc-mediated growth inhibition (Laby et al, 2000). Here, we investigated whether the regulation of Fe deficiency responses by Suc was associated with the aforementioned Suc signaling components by using snrk1.1, snrk1.2, rsr1, sun6, and isi4 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…The complex links between plant growth, primary metabolism, and flowering time in Arabidopsis are highlighted in a recent article where increased plant growth was positively associated with early-flowering phenotypes (El-Lithy et al, 2010), which may explain the larger rosette area observed prior to flowering in 30-d-old agl22 mutant plants compared with the wild type ( Figure 9A; Supplemental Figure 9B). In addition, starch/ carbohydrate status and metabolite levels have been linked to rosette growth Sulpice et al, 2009), as well as development and flowering time (Zhou et al, 1998;Moore et al, 2003;Funck et al, 2012). Both photosynthesis and flowering are regulated by the light environment and are clearly linked via the carbohydrate status (Zhou et al, 1998;Moore et al, 2003;Funck et al, 2012), connecting primary metabolism with plant growth and development.…”
Section: A Flowering Time Gene Influences Water Use and Photosynthesimentioning
confidence: 99%
“…In addition, starch/ carbohydrate status and metabolite levels have been linked to rosette growth Sulpice et al, 2009), as well as development and flowering time (Zhou et al, 1998;Moore et al, 2003;Funck et al, 2012). Both photosynthesis and flowering are regulated by the light environment and are clearly linked via the carbohydrate status (Zhou et al, 1998;Moore et al, 2003;Funck et al, 2012), connecting primary metabolism with plant growth and development. However, little is known about the link between photosynthetic performance and flowering time especially in flowering time mutants, and at this point, it is unclear why the agl22 mutants exhibited a substantial reduction in photosynthesis already under well-watered conditions.…”
Section: A Flowering Time Gene Influences Water Use and Photosynthesimentioning
confidence: 99%
“…In plants, sugar levels influence many developmental phases from seed germination (Pego et al, 1999;Price et al, 2003;Li et al, 2012) to flowering induction (van Dijken et al, 2004;Funck et al, 2012;Wahl et al, 2013) to senescence (Veyres et al, 2008;Wingler et al, 2010Wingler et al, , 2012Thomas, 2013). By taking advantage of the effects of externally supplied sugars on Arabidopsis (Arabidopsis thaliana) growth, genetic screens have often been used to identify mutants with altered responses to sugars (Zhou et al, 1998;Rolland et al, 2002;Rook and Bevan, 2003;Baier et al, 2004;Gibson, 2005).…”
mentioning
confidence: 99%